Pengaruh Metode Tamyiz Terhadap Penguasaan Kosakata Mata Pelajaran Bahasa Arab Siswa Kelas V SDI Al-Azhar 47 Samarinda - Aidah, Adhe Nor; Hidayat, Ahmad Fadhel Syakir; Annisa, Maryam Nur (Faculty of Education and Teacher Training of UINSI Samarinda, 2023)
Abstract To improve the Arabic vocabulary mastery of elementary school students, an effective teaching method is needed. One method that can be used is the Tamyiz method, which involves grouping words based on certain concepts or themes. This study aims to determine the effect of applying the Tamyiz method on the Arabic vocabulary mastery of students at SDI Al-Azhar Samarinda. The research method used was quantitative research with a total sampling technique on all fifth-grade students at SDI Al-Azhar Samarinda. Data were collected through questionnaires, interviews, and documentation. The results of the data analysis showed that there was a positive and significant relationship between the application of the Tamyiz method and the Arabic vocabulary mastery of students, with a moderate correlation level and a coefficient of determination of 29.8%. Therefore, it can be concluded that maximizing the use of the Tamyiz method can have a positive effect on the Arabic vocabulary mastery of elementary school students. The Tamyiz method helps students organize vocabulary based on certain concepts or themes, making it easier for them to remember and connect new vocabulary with existing ones. Therefore, it is necessary to optimize the use of the Tamyiz method so that students can continue to practice mastering Arabic vocabulary. Keywords: Effect, Arabic Vocabulary, Tamyiz Method Abstrak Untuk meningkatkan penguasaan kosakata bahasa Arab siswa SD, diperlukan metode pengajaran yang efektif. Salah satu metode yang dapat digunakan adalah metode Tamyiz, yaitu metode pengelompokkan kata berdasarkan konsep atau tema tertentu. Penelitian ini bertujuan untuk mengetahui pengaruh penerapan metode Tamyiz terhadap penguasaan kosakata bahasa Arab siswa di SDI Al-Azhar Samarinda. Metode penelitian yang digunakan adalah penelitian kuantitatif dengan teknik total sampling terhadap seluruh siswa kelas V di SDI Al-Azhar Samarinda. Data dikumpulkan melalui angket, wawancara, dan dokumentasi. Hasil analisis data menunjukkan bahwa terdapat hubungan positif dan signifikan antara penerapan metode Tamyiz dengan penguasaan kosakata bahasa Arab siswa, dengan tingkat korelasi sedang dan koefisien determinasi sebesar 29,8%. Dengan demikian, disimpulkan bahwa memaksimalkan penggunaan metode Tamyiz dapat memberikan efek positif pada penguasaan kosakata bahasa Arab siswa SD. Metode Tamyiz membantu siswa dalam mengorganisasi kosakata berdasarkan konsep atau tema tertentu, sehingga mempermudah siswa dalam mengingat dan menghubungkan kosakata baru dengan yang sudah ada. Oleh karena itu, diperlukan pengoptimalan kembali penggunaan metode Tamyiz agar siswa dapat terus berlatih dalam penguasaan kosakata bahasa Arab. Kata kunci: Pengaruh, Kosakata Bahasa Arab, Metode Tamyiz